A comparative study of the efficacy of topical 10% curcuma aeruginosa solution and topical 5% minoxidil solution on the treatment of male androgenetic alopecia - Sriviriyakul, Pirada; Chokdeesumrit, Wipapen (Journal of Medicine and Health Sciences, 2020)
Topical minoxidil is a standard treatment for androgenetic alopecia. But the limiting factors are its side effects, such as contact dermatitis, hypertrichosis, etc. Topical 10% Curcuma aeruginosa is a botanically derived inhibitor of 5α-reductase that can stimulate hair growth. To compare the efficacy of topical 10% Curcuma aeruginosa solution versus topical 5% minoxidil solution, we enrolled 24 men ages 18-60 with Hamilton–Norwood types II–IV androgenetic alopecia. Subjects were randomly allocated to receive either topical 10% Curcuma aeruginosa solution or topical 5% minoxidil solution apply vertex twice daily for 12 weeks. Participants were followed up every 4 weeks. Efficacy was evaluated by target area hair count, hair diameter, ratio of vellus hair and terminal hair, global photographic review scores and patients’ subjective assessments of hair regrowth. Twenty-one subjects were able to complete the study with average age 38.62 ± 10.14 years. At 12 week, Mean of ratio of vellus hair and terminal hair in topical 10% Curcuma aeruginosa solution group were significantly decrease from baseline when compared with topical 5% minoxidil solution group. (p=0.026). But mean of target area hair count and hair diameter, global photographic review scores and patients’ subjective assessments of hair regrowth were not signficantly different. There were no serious adverse events during the study. Therefore topical 10% Curcuma aeruginosa solution is effective and safe for increasing hair growth. It can be used as alternative treatment for male androgenetic alopecia.